The effect of load and technique on biomechanical and perceptual responses during dynamic pushing and pulling - Desai, Sheena Dhiksha (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2009)
Changes in the industrial job profile, from lifting and lowering to repetitive dynamic pushing and pulling have been facilitated through the use of manual vehicles, aimed at minimising the workload. Yet, the demands of pushing and pulling have not been well documented. Using measures of the horizontal component of the hand forces, spinal kinematics, muscle activity at various sites on the upper body and body discomfort ratings, this study aimed at quantifying the biomechanical and perceptual demands of various dynamic push/pull techniques. 36 healthy male participants performed two-handed forward pushing, two-handed backward pulling and one-handed forward pulling, employing an industrial pallet jack supporting two loads of 250kg or 500kg. While no single technique was definitively identified as preferable regarding hand forces, pushing at 500kg elicited higher initial and sustained forces (p<0.05) than one- and two-handed pulling respectively. Increments in load mass from 250kg to 500kg resulted in significant differences in the initial, sustained and ending forces. With regard to spinal kinematics in the sagittal plane, two-handed pulling elicited the highest trunk flexion, and may therefore expose individuals to prolonged forward bending. Generally this technique was found to evoke the highest sagittal responses. Spinal kinematic measures in the lateral and transverse planes suggested that one-handed pulling was accompanied by the highest measures, and hence the greatest risk of developing lower back disorders related to this plane. Although various combinations of muscles were active during each technique, one-handed pulling and pushing, most often induced the highest muscle activation levels and two-handed pulling, the lowest. While erector spinae evidenced no significant differences between techniques at each load or between loads for the same technique, activation levels were high under all conditions. Perceptual ratings of body discomfort revealed that not only is the upper body susceptible to injuries during pushing and pulling, but also that the lower extremities may have a considerable role to play in these tasks, with the calves being a particular area of concern. Findings concluded that symmetrical pushing and pulling tasks are preferable.
Keywords: Work -- Physiological aspects; Biomechanics; Human engineering; Lifting and carrying